Pendidikan Susila Sebagai Upaya Pembentukan Karakter Pancasila Perspektif Sarasamuscaya - Santha, I Made Surya (Metta : Jurnal Ilmu Multidisiplin, 2024)
The ongoing development of the times has made many changes not only positive but also negative. This negative change is due to the lack of a strong foundation as a barrier between existing cultural understandings and new cultures that continue to develop. The foundation that is not strong makes the moral values and moral order of the nation's philosophy eroded. Strengthening morals and character is necessary to maintain the values of Pancasila as a view of life. The role of moral education is one of the efforts that can be used in reinstilling the character of pancasila. Sarasamuscaya is one of the guidelines that can be referred to to understand morality in the formation of a characterful personality. The purpose of this study is to analyze how moral education as an effort to build the character of pancasila view sarasamuscaya. The research method used is a descriptive qualitative method with a literature study approach that focuses on sarasamuscaya by adhering to strengthening the character of Pancasila. Overall, this study found that there is a close relationship with how moral education in sarasamuscaya there is a principle that can be used as a guideline, namely tri kaya parisudha, which is three actions based on dharma to be done. The conclusion that can be drawn is that morals are a form of personality that transmits character, the character of Pancasila in education is currently the focus of the formation of quality students, and in its efforts inner moral education with the principle of Tri Kaya Parisudha in sarsamuscaya can be used as a basis for strengthening the character of Pancasila.